Competences Expected and Gained during the Teaching Practicum: Analysis of Three Competence Areas Affected during the Pandemic - Josué Prieto-Prieto; Javier Cruz-Rodríguez; Blanca García-Riaza; María José Hernández-Serrano (MDPI AG, 2024)
This study analyzes three competency areas promoted in the Practicum during the 2020-2021 and 2021-2022 academic years: pedagogical and didactic competences, coexistence and participation management and collaborative work. To this end, using a non-experimental design, data were collected from a sample of 725 Education students from University of Salamanca with the aims of determining the students' expectations about the Practicum prior to its development and of measuring its impact on the students during its development or the influence of the context imposed during the COVID-19 pandemic. The research was contextualized in two Practicum subjects included in the curricula of the bachelor's degrees in Early Childhood/Primary Education at the University of Salamanca. Both degrees are taught at three different university centers, Ávila, Salamanca and Zamora. The results revealed the importance of the preparation of the students in their university training period with regard to the first competence area, together with the perceptions of the students about what they learnt in the competences of areas 2 and 3. Relevant conclusions were drawn about their learning expectations towards the second area and the problems caused by the pandemic in order to develop communication skills with students and families.